Human manipulative behavior in the Central European Late Eneolithic and Early Bronze Age: humeral bilateral asymmetry - Sládek, Vladimír; Berner, Margit; Sosna, Daniel; Sailer, Robert (American journal of physical anthropology, 2007)
It is assumed that the transition from the Late Eneolithic to the Early Bronze Age in Central Europe was associated with substantial changes in subsistence and the perception of gender differences. However, the archeological record itself does not entirely support this model. Alternatively, this transition may be interpreted as a continuous process. We used asymmetry in external dimensions, and asymmetry in size and distribution of cortical tissue of humeri to elucidate the nature of this transition with respect to differences in manipulative behavior. The total sample of 67 individuals representing five archaeological cultures was used. The results indicate that the pattern of asymmetry of the humeral external measurements and the cross-sectional parameters taken at 35% of humeral biomechanical length remain stable during the Late Eneolithic and Early Bronze Age. However, females of both periods show fluctuating asymmetry for all of the cross-sectional parameters, but directional asymmetry for biomechanical length. Males are nonsignificantly shifted from the line of equivalence for biomechanical length, but exhibit directional asymmetry for the cortical area and polar moment of area. Only distal articular breadth yields fluctuating asymmetry for both females and males in both periods. Thus, the transition from the Late Eneolithic to the Early Bronze Age can be seen as a continuous process that probably affected only a limited part of human activities. We interpret the differences between females and males of both periods as evidence of gender-specific activities; males might have been associated with extra-domestic agricultural labor that resulted in asymmetrical manipulative loading and females with domestic labor with symmetrical manipulative loading in both periods.
Keywords: Stress, Mechanical; humerus; lidé; Behavior; chování; Sex Characteristics; Evropa; mechanický stres; Humerus; Female; Humans; Male; pohlavní dimorfismus; mužské pohlaví; Weight-Bearing; Europe; ženské pohlaví; zatížení muskuloskeletálního systému